Proceeding of international crop Science Symposium October 17-20, 1984, Fukuoka, Japan (Fukuoka, Japan, 1984)
These papers covered the general subjects of rice productivity associated with basic studies in crop phisiology, ecology and morphology
Keywords: Rice,Nghiên cứu lúa gạo Đông Á; Research